Strabon i Rzym - Wróbel, Małgorzata (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The article presents information about Rome as given in the Geography of Strabo.
Keywords: Strabon; geografia grecka; starożytny Rzym